Articulating Migrantok Taiwan-based Filipino factory workers’ multimodal expressions of sacrifice on TikTok - Jimenez, Jandale D.; Osorio, Maria Jeriesa P. (Quezon City University of the Philippines Diliman, 2025)
The Philippines had long relied on labor migration, with Overseas Filipino Workers (OFWs) celebrated as bagong bayani or modern-day heroes. While the sacrifices of domestic workers had been widely studied, those of Filipino factory workers remained largely overlooked. This study explored how Filipino factory workers in Taiwan used TikTok to narrate their sacrifices in a transnational and mediated sense. Drawing on need sacrifice (Holding et al., 2019) and multimodal digital coherence (Meier, 2022), the research examined how migrants expressed sacrifice through TikTok’s affordances, focusing on maintenance routines, psychological struggles, and lost leisure, shaped by their social and personal contexts. Using a qualitative approach, the study analyzed 45 TikTok posts and conducted 15 in-depth interviews with migrant workers based in Taiwan. Findings showed that TikTok served not only as a space for entertainment, but also as a digital diary of their sacrifice and endurance. Through captions, visuals, sounds, and trends, migrant workers portrayed sacrifice as material, emotional, and temporal, embedded in their daily transnational life. For them, TikTok functioned as a space to assert agency, foster solidarity, and resist stereotypes. This work contributes to migration and media studies by illustrating how digital storytelling enabled marginalized workers to humanize their labor and own their narrative at the face of global precarity.
Undergraduate thesis
Keywords: Foreign workers, Filipino -- Taiwan -- Social conditions; Migrant labor -- Philippines; TikTok (Electronic resource).; Internet videos; Online social networks